Reduced affinity of the androgen receptor for 5 alpha-dihydrotestosterone but not methyltrienolone in a form of partial androgen resistance. Studies on cultured genital skin fibroblasts. - Pinsky, L (1985)
We have studied a child with posterior labial fusion, clitoral phallus, female urethra, and a short, blind vagina born to a mother with decreased axillary and pubic hair. Her karyotype is 46,XY. At 2 yr of age, the child's basal level of plasma testosterone was less than 0.35 nM and after human chorionic gonadotropin stimulation, it rose to 2.6. Testis and epididymis histology were normal. Her cultured genital (labial) skin fibroblasts have normal testosterone 5 alpha-reductase activity, and metabolize 5 alpha-dihydrotestosterone (DHT) normally, but they do not augment (up-regulate) their basal androgen-receptor binding activity during prolonged incubation with DHT. With DHT, the androgen receptor in her genital skin fibroblasts has a normal binding capacity (maximum binding capacity = 25 fmol/mg protein), but an increased rate constant of dissociation (k = 11.6 X 10(-3) min-1; normal, 6 +/- 1.2 (+/- SD)), and a decreased apparent equilibrium binding affinity (Kd = 0.6 nM; normal, 0.22 +/- 0.09) that is evident in the results of 2-h assays but not of those lasting 0.5 h. With the synthetic androgen, methyltrienolone, all three binding properties of the receptor are normal, and her receptor activity up-regulates normally. We interpret these results to mean that the subject has a ligand-selective defect in the time-dependent transformation of initial, low-affinity androgen-receptor complexes to serial states of higher affinity, presumably as the result of a structural mutation at the X-linked locus that encodes the androgen receptor protein.